2022
DOI: 10.3390/ma15124140
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Formability Prediction Model for Aluminium Sandwich Panels with Polymer Core

Abstract: In the present work, the compatibility relationship on the failure criteria between aluminium and polymer was established, and a mechanics-based model for a three-layered sandwich panel was developed based on the M-K model to predict its Forming Limit Diagram (FLD). A case study for a sandwich panel consisting of face layers from AA5754 aluminium alloy and a core layer from polyvinylidene difluoride (PVDF) was subsequently conducted, suggesting that the loading path of aluminium was linear and independent of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Liu et al [11] presented an analytical formability model for the sandwich panel and demonstrated its capability by predicting the critical failure of a sandwich panel consisting of two skin AA5754 layers and a core PVDF layer as a case study. It was found that the developed FLD model overcame the limitation of traditional FLD models and was capable of predicting the formability of sandwich panels made from composite materials.…”
mentioning
confidence: 99%
“…Liu et al [11] presented an analytical formability model for the sandwich panel and demonstrated its capability by predicting the critical failure of a sandwich panel consisting of two skin AA5754 layers and a core PVDF layer as a case study. It was found that the developed FLD model overcame the limitation of traditional FLD models and was capable of predicting the formability of sandwich panels made from composite materials.…”
mentioning
confidence: 99%